AI for personalized medicine - Lewis, Aidan Michael, author; Bailey, Susan M., advisor; LaRocca, Tom J., committee member; Nishimura, Erin O., committee member (Colorado State University. Libraries, 2023)
In 2021, Americans spent an estimated $4.3 trillion dollars on healthcare, an extraordinary amount for treatment that is often less effective than care in other developed nations (1-3). Precision, or personalized, medicine represents a new frontier in healthcare that promises treatment plans and optimized health strategies tailored to an individual (4) thereby making medicine more effective and less costly. Contemporary Artificial Intelligence (AI) and Machine Learning (ML) approaches have tremendous potential to advance the field of precision medicine by leveraging the technology's power of deciphering patterns in the data to make predictions about an individual's health outcomes (3, 5-8). However, many developing AI/ML approaches to precision medicine have not proven particularly successful in making accurate predictions and conclusions mostly due to the limited availability of high-quality medical data for input. The Wake Forrest University Non-Human Primate Radiation Late Effects Cohort (NHP RLEC) provides an unprecedented opportunity to test AI's ability to be trained on a comprehensive human health analog data set in an experimentally irradiated Rhesus monkey cohort with extraordinary life-time records of biomarker levels and health outcomes. Here, we test prevalent, scalable ML models to improve accuracy of predictions specifically related to radiation biomarkers, dose, and health outcomes. We find that CatBoost, ElasticNet, and XGBoost models can accurately predict lymphocyte counts for both monkey populations and individual monkeys. Furthermore, these models can accurately predict radiation dose and biomarker levels using only five other features within the models. Although the models were only marginally successful at predicting lymphocyte counts using radiation-related data alone, and at predicting the health outcomes of the monkeys, these findings and this unique dataset represent key steps toward refining the combinations of factors necessary for the successful use of AI/ML models in precision medicine for humans.
Keywords: artificial intelligence; medicine; space; astronautics; AI; radiation